The effect of covid-19 pandemic onconsumer shopping habits: case study ofuniversity students - CEVİZ, NURAY (My University, 2022)
The changing shopping habits gained speed with the Covid-19 pandemic and online shopping sites started to be used more. The application development process has gained momentum and web interface designs have tended to keep individuals staying at home in quarantine more on the screen and to shop more. The effect of the Covid-19 pandemic on consumers’ shopping habits was examined within the scope of this research. For this purpose, university students were taken as a sample and a survey was developed to understand the impact of the pandemic. The research was carried out with the participation of 257 people in otal. The questionnaire was administered online via e-mail and social media. Survey questions, along with questions containing demographic features, include hedonistic behavior developed by Babin, Darden and Griffin (Babin et al., 1994), impulsive behavior developed by Rook and Fisher (Rook and Fisher, 1995), and social media and advertising questions developed by us. The data obtained from the questionnaire containing 5-point Likert type questions were evaluated in statistical package programs. According to the results of the research obtained by the interpretation and evaluation of the data; the Covid-19 pandemic has had an impact on the shopping habits of consumers in the sample of university students. 85.3% of the participants stated that they used online shopping sites during the pandemic. The basic need, food shopping (23%) has left its place to clothing with 34.2%. While there was a great increase in online food shopping, which was the basic need at the beginning of the pandemic, it was seen that clothing shopping came to the fore in the following period. As a result, it has been seen that there has been a great change in people’s consumption shopping methods compared to the period before the pandemic, and the pandemic has affected the growth of online shopping with great acceleration.

Bu araştırma kapsamında Covid 19 pandemisinin tüketicilerin alışveriş alışkanlıklarına etkisi incelenmeye çalışılmıştır. Bu amaç doğrultusunda üniversite öğrencileri örneklemi alınmış ve pandeminin etkisini anlayabilmek için bir anket geliştirilmiştir. Araştırma toplam 257 kişinin katılımıyla gerçekleştirilmiştir. Anket elektronik posta ve sosyal medya aracılığıyla çevrimiçi olarak uygulanmıştır. Anket soruları demografik özellikler içeren sorular ile birlikte, Babin, Darden ve Griffin (Babin ve ark., 1994) tarafından geliştirilen hedonist davranış, Rook ve Fisher (Rook ve Fisher, 1995) tarafından geliştirilen iç tepkisel davranış ve tarafımızdan geliştirilen sosyal medya ve reklam soruları içermektedir. 5’li likert tipi sorular içeren anketten elde edilen veriler istatistiksel paket programlarda değerlendirilmiştir. Verilerin yorumlanması ve değerlendirilmesi ile elde edilen araştırma sonuçlarına göre; Covid 19 pandemisinin üniversite öğrencileri örneklemindeki tüketicilerin alışveriş alışkanlıklarına etkisi olmuştur. Araştırmaya katılanların %85.3’ü pandemi sürecinde online alışveriş sitelerini kullandıklarını belirtmişlerdir. Burada şaşırtıcı olan temel ihtiyaç olan gıda alışverişinin (%23) ilk sırayı %34,2 ile giyime yerini bırakmış olmasıdır. Pandeminin başlangıcında temel ihtiyaç olan online gıda alışverişinde büyük artış görülürken ilerleyen dönemde giyim alışverişinin daha fazla ön plana çıktığı görülmüştür. Sonuç olarak pandemi öncesindeki döneme göre insanların tüketim alışveriş yöntemlerinde büyük bir değişim olduğu, pandeminin online alışverişin çok büyük bir ivme ile büyümesine etki ettiği görülmüştür.
Covid 19 pandemisinin tüketici alışveriş alışkanlıklarına etkisi: üniversite öğrencileri örneği
Keywords: Consumer Behaviors; Pandemic Effect; Online Shopping; Tüketici Davranışı; Salgın Etkisi; Çevrimiçi Alışveriş